Current issues in research communications: open access – the view from the academy - 4th report to JISC, March 2011 - Hubbard, Bill; Hodgson, Amanda; Fuchs, Willow (Centre for Research Communications, 2011)
The topic of this report is the attitude of academic and research support staff in to Open Access: what may dissuade them from adopting it and what might persuade them of its value. It looks at the following questions: • What do researchers and support staff think about Open Access? • Is there an alternative they might prefer? • How might future OA advocacy be addressed?